Thermal Stratification Characteristics of Storage Tanks on Solar Water Heater Inserted with Latent Heat Material - Nadjib, Muhammad; Wahyudi, Wahyudi; Santosa, Tito Hadji Agung; Hidayat, Yaafi (Universitas Muhammadiyah Yogyakarta, 2024)
As a latent heat medium, phase change material (PCM) can be applied to heat storage for solar water heaters (SWH). The method used to place PCM is to put it in a capsule. Thermal stratification is critical in generating SWH thermal efficiency. Installation of horizontal capsules in the tank has no known effect on thermal stratification. This paper aims to study the thermal stratification in active-type SWH incorporating PCM. A cylindrical capsule containing the PCM was placed inside the tank. The thermocouple was installed on both the water and PCM sides. The charging process was conducted indoors, and the water flow rate varied from 1, 2, and 3 LPM. Water temperature data for each variation was analyzed to evaluate the thermal stratification. Richardson number analysis proved that thermal stratification was formed in all water flow rates. It was found that a low water flow rate results in high thermal stratification.